Transformational Leadership and Work Environment on Employee Performance through Job Satisfaction in the Digital Transformation - Joddy Hernady; Brina Mariana; Acep Arna Hikmat; M. Kamal Satria; Rahma Wahdiniwaty; Deden Abdul Wahab Sya’roni (LifeSciFi, 2026)
Rapid digital transformation has increased the need for organizations to effectively manage human resources to sustain employee performance. This study examines the effect of transformational leadership and work environment in enhancing employee performance through job satisfaction as a mediating variable within the context of digital transformation. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling with data collected from 125 employees in Bandung, West Java. The findings reveal that transformational leadership and work environment have positive and significant effects on job satisfaction and employee performance. Job satisfaction also demonstrates a significant positive influence on employee performance and acts as a partial mediator in the relationships between transformational leadership and employee performance, as well as between work environment and employee performance. These results indicate that effective leadership and a supportive work environment not only directly improve performance but also indirectly enhance it through increased employee satisfaction. From a managerial perspective, the study highlights the importance of integrating human-centered leadership practices and conducive workplace conditions to strengthen organizational performance in the digital era.